A Needs and Resource Assessment of Continuing Medical Education in Haiti - Marisa Nádas; Rachel Bedenbaugh; Michelle Morse; Graham T. McMahon; Christine L. Curry (Ubiquity Press, 2015)
Background: Haiti has a chronic physician shortage, and the country has been facing an increased disease burden since the 2010 earthquake and the subsequent introduction of cholera. In such resource-challenged settings, access to postgraduate medical education often is limited due to inadequate financial, structural, and academic resources. A crucial component to improved health in Haiti is the expansion of continuing medical education (CME). To our knowledge there have been no previous studies investigating the continuing professional development needs of Haitian physicians working in this context. Objective: The objectives of this study are to describe the educational resources available to Haitian physicians and to understand their continuing professional development needs. Methods: We performed a needs and resource assessment of CME available to Haitian physicians using surveys and focus groups. We surveyed 62 physicians and led 3 focus groups. Questions gathered data on physicians' access to educational resources. Descriptive statistics were calculated from surveys, and focus group transcripts were manually reviewed for themes. Findings: In all, 82 conference attendees were invited to participate. Of these, 62 physicians completed the needs and resource assessment survey. Of the participants, 16% had a medical library at work and 31% had access to a computer at work. Educational conferences were available at work for 27% of participants, and 50% attended conferences outside of work. Less than half (45%) identified a clinical mentor. Focus group participants described inadequate tangible and reference resources, lack of colleague support, and lack of avenues for specialty training and employment. Conclusions: In this needs assessment, Haitian physicians identified lack of support for clinical decision making, poor access to CME activities, limited professional development, and absence of employment opportunities as key areas of need in support of their clinical and professional work.